1989
DOI: 10.1111/j.1365-2044.1989.tb11167.x
|View full text |Cite
|
Sign up to set email alerts
|

Postdural puncture headache A comparison between 26‐ and 29‐gauge needles in young patients

Abstract: Summary The incidence of postdural puncture headache after spinal anaesthesia with two types of 26‐ and 29‐gauge needles was investigated in 149 patients less than 30 years old. Ten patients, (6.7%), six men and four women, developed typical symptoms of postdural puncture headache, while six (4.0%) developed headache of other origin. There were no headaches in the 29‐gauge group. Spinal anaesthesia in four patients (8%) was impossible to perform with the 29‐gauge needle. By using the latter, spinal anaesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0
6

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 9 publications
5
76
0
6
Order By: Relevance
“…We did not find a significant difference in the present study, but this may be due to the rather small group size. Most previous studies concerning PDPH were done in spinal anaesthesia with smaller needles [12][13][14][15]. Large needle size is definitely associated with more frequent PDPH [10,11,16].…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a significant difference in the present study, but this may be due to the rather small group size. Most previous studies concerning PDPH were done in spinal anaesthesia with smaller needles [12][13][14][15]. Large needle size is definitely associated with more frequent PDPH [10,11,16].…”
Section: Discussionmentioning
confidence: 99%
“…16 Many of the headaches that occur after spinal anaesthesia may not be the result of dural puncture and should be differentiated from the PDPHs by the patient's history. 13,25 The relatively high rate of PDPH that we describe for both spinal needles requires explanation. When the present study is compared with others using the 27 gauge Quincke needle, it appears that the patients in the present study were younger and followed up more closely than those reported by Flanagan et al 1 (PDPH rate of 3.7%).…”
Section: Discussionmentioning
confidence: 93%
“…2,15,~9,24-27 While use of the 29 gauge Quincke needle has been reported to result in an incidence of PDPH between 0% and 2%, the failure rate of between 1.2% and 8% may make its use impractical. 20,24,25,28,29 Variability in the reported frequency of PDPH may be a result of differences in patient populations, such as age and sex 2,~2 or intraoperative variables such as patient position, bevel orientation, t4,3~ type and baricity of anaesthetic agent, 26 addition of opioid 31 and intraoperative sedation. 7 The psychosomatic component of PDPH should be considered 32,33 as well as the definition of PDPH used and the method of patient follow-up employed.…”
Section: Discussionmentioning
confidence: 99%
“…This is further facilitated by not using introducer needle. The incidence of headache using 26 G spinal needle, has variably been reported as 0.4%, 7.5% and 37.2% by different authors [14,15,16]. This wide range of variation may be due to factors like age, sex.…”
Section: Discussionmentioning
confidence: 99%